Oxaliplatin versus irinotecan as first-line therapy in metastatic colorectal cancer with prior adjuvant treatment: a retrospective study on efficacy, sequential therapy, and the impact of thrombocytopenia - Shan, Han; Huang, Shuohan; Zhou, Changming; Wang, Mengmeng; Du, Qiong (Frontiers in Oncology, 2025)
BackgroundThe comparative efficacy of oxaliplatin versus irinotecan as first-line therapy in mCRC patients with prior adjuvant treatment remains unclear.ObjectivesTo compare the efficacy of first-line oxaliplatin-based versus irinotecan-based chemotherapy in metastatic colorectal cancer (mCRC) patients with prior adjuvant treatment and explore factors influencing survival outcomes.MethodsThis retrospective single-center study analyzed 227 mCRC patients (2005–2014) receiving oxaliplatin (n=106) or irinotecan (n=121) as first-line therapy. Survival outcomes, treatment sequences, and adverse events were evaluated via multivariate analysis.ResultsCompared with the irinotecan group, the oxaliplatin group had a numerically longer median OS (29.9 vs. 23.0 months; HR = 0.75, p = 0.043) but comparable PFS (9.2 vs. 9.4 months; p = 0.722). Subgroup analysis confirmed consistent OS benefits with oxaliplatin regardless of prior adjuvant regimens. The chemotherapy interchange rates differed significantly (47% oxaliplatin→irinotecan vs. 28% irinotecan→oxaliplatin, p = 0.004), although the treatment sequence did not affect OS (30.4 vs. 32.1 months; p = 0.351). Thrombocytopenia during prior adjuvant therapy was more common in the irinotecan group (29% vs. 15%, p = 0.016), which was correlated with oxaliplatin avoidance in subsequent lines. Multivariate analysis revealed that thrombocytopenia itself was not an independent risk factor but influenced treatment selection.ConclusionDespite the limitations of a retrospective, single-center design, first-line oxaliplatin provides superior OS in mCRC patients with prior adjuvant therapy, independent of the treatment sequence. The OS disparity stems from the differential use of chemotherapy interchange, driven by oxaliplatin-induced thrombocytopenia during adjuvant treatment, which may lead to premature regimen abandonment. Clinicians should prioritize thrombocytopenia prevention and avoid arbitrary oxaliplatin discontinuation. These findings highlight the importance of managing oxaliplatin-associated toxicity to preserve subsequent treatment options, though they require validation in prospective studies.